Stick to the Plan? A Revealed-Preference Study of Behavioural Impacts of Traffic Information - Yin-Yen Tseng; Jasper Knockaert; Erik T. Verhoef (Tinbergen Institute, 2010)
We estimate a revealed-preference scheduling model of morning peak behaviour that allows us to determine the impact of traffic information on traveller behaviour. Specifically, we distinguish between the marginal impact of expected travel times versus that of deviations from this expectation upon user behaviour. We find that participants that chose to receive a smart-phone with traffic information as a reward in our experiment respond to the deviation of actual travel times from the expectation, which they did not do before. This we interpret as evidence that traffic information indeed affects behaviour. We also find that participants who did not choose the smart-phone, but instead opted for monetary rewards, also respond to the deviation of actual travel times from the expectation. This suggests that these drivers use other sources of information to help their trip planning.
Keywords: R41; D12; 330; Traffic Information; Discrete Choice Analysis; Revealed Preference; Value of Travel Time Savings; Value of Schedule Delay; Transportzeit; Informationswert; Verkehrsverhalten; Diskrete Entscheidung; Offenbarte Präferenzen; Theorie